Charitable giving by the poor: A field experiment in Kyrgyzstan - Maja Adena; Rustamdjan Hakimov; Steffen Huck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
Previous studies of charitable giving have focused on middle- or high-income earners in Western countries, neglecting the poor, although the lowest income groups are often shown to contribute substantial shares of their income to charitable causes. In a large-scale natural field experiment with over 180,000 clients of a micro-lending company in Kyrgyzstan, we study charitable giving by a population that is much poorer than the typical donors studied so far. In a 2x2 design, we explore two main (pre-registered) hypotheses about giving by the poor: (i) that they are more price sensitive than the rich such that, in contrast to previous studies, matching incentives induce crowding in of out-of-pocket donations; (ii) that they care about their proximity to the charitable project. We find evidence in favor of the former but not the latter.
Keywords: C93; D64; D12; 330; Charitable giving; field experiments; matching donations